2011
DOI: 10.1177/1744259111429781
|View full text |Cite
|
Sign up to set email alerts
|

Properties and microstructure of porous ceramic bodies containing fly ash

Abstract: Effect of two kinds of fly ash collected from the thermal power plants on the green properties and sintering behavior of clay ceramic tile bodies was investigated. Flow time, unit weight, color difference, water absorption, flexural strength, and linear shrinkage of the ceramic samples with four different fly ash percentages of replacement with feldspath varying between 0% and 20% by weight were determined. Furthermore, thermal characterization and morphology of phases of selected ceramic compositions were stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Considering the lightness factor in CFA-containing brick samples, it was observed that there was a slight fluctuation differently from the samples with SFA. The rise in the lightness factor of brick samples is due to the decline in the amount of Fe 2 O 3 and organic materials (Kockal, 2012a). Thus, the increment in the lightness factor of SFA-containing brick samples was based on extreme Fe 2 O 3 content even higher than the clay as seen in table 1.…”
Section: Resultsmentioning
confidence: 93%
“…Considering the lightness factor in CFA-containing brick samples, it was observed that there was a slight fluctuation differently from the samples with SFA. The rise in the lightness factor of brick samples is due to the decline in the amount of Fe 2 O 3 and organic materials (Kockal, 2012a). Thus, the increment in the lightness factor of SFA-containing brick samples was based on extreme Fe 2 O 3 content even higher than the clay as seen in table 1.…”
Section: Resultsmentioning
confidence: 93%
“…All these characteristics of clay have made it among the first choice in many recent 3D printing architectural projects, along with concrete and other adobe-based materials [ 20 , 21 , 22 ]. Most of the clay building materials include illite along with quartz, feldspar, carbonates and iron oxides [ 23 , 24 , 25 , 26 ]. Preparation of illite-based ceramics is based on firing the ceramic bodies at temperatures from 700 °C to 1100 °C, which solidifies the ceramic body and enables its sufficient mechanical strength.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, the volume coloring of the product, especially in the case of obtaining saturated color tones, requires an increased consumption of coloring additives, which increases its cost. Reducing the cost of the product in this case is possible due to the use in the compositions of the masses of man-made wastes containing in enough quantity color-forming oxides necessary to give the material the desired color [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. The choice of pigments is determined by the properties of the pigment and material, the nature of their interaction, as well as the processing parameters and operating conditions of the products.…”
Section: Introductionmentioning
confidence: 99%